Comparison of physiological responses between a W´ BAL-INT training model and a critical power test - Galán-Rioja, M. Á.; González-Mohíno, F.; Abián-Vicen, J.; Gonzalez-Ravé, J. M. (Journal of Human Kinetics, 2024)
This study aimed to compare acute physiological responses during the W prime (W´) balance training model (W´BAL-INT) with performance in the critical power test (CPTest). Additionally, the study sought to determine the extent of neuromuscular and metabolic fatigue associated with severe and extreme intensity domains. Fourteen road master cyclists (13 male, 1 female) completed graded incremental exercise tests to determine their maximum oxygen uptake and 12-, 7- and 3-min maximal efforts to assess CP and W´ (CPTest). Additionally, they participated in a reconstitutive intermittent training session following the W´BAL-INT model. Physiological responses including oxygen uptake (VO2), the heart rate (HR), blood lactate (BLa¯) concentration, and perceptual responses (RPE), were measured and compared to CPTest performance data. The W´BAL-INT induced steady-state physiological responses in VO2mean (F = 0.76, p = 0.655) and absolute HR, relative HR and HRCP (F = 0.70, p = 0.704; F = 1.11, p = 0.359; F = 1.70, p = 0.095, respectively) comparable to CPTest. During the 3-min work intervals in the training session, VO2 was stable and similar to VO2peak (54.2 ± 6.7 to 59.3 ± 4.9 ml·kg-1·min-1) in the CPTest. Furthermore, 4-min rest intervals facilitated recovery up to moderate fatigue levels (80-100% of W´ balance). HR responses were sensitive to interval intensity and accumulated time. Meanwhile, BLa¯ responses and the RPE increased fatigue development during W´BAL-INT. The W´BAL-INT training model generates consistent physiological responses in mean oxygen kinetics, the percentage of CP and the HR, similar to those observed during the CPTest. However, different physiological responses were observed in peak oxygen kinetics and W´ energy balance.